{Magnetic resonance imaging visualization of a vaginal septum} - Papaioannou, G.; Koussidis, G.; Michala, L. (Fertility and Sterility, 2011)
Magnetic resonance imaging is considered the gold-standard imaging technique in cases of Müllerian and vaginal anomalies, however, vaginal delineation often proves difficult, owing to the fact that vaginal walls are normally collapsed and in close proximity. Instilling gel through the introitus allows for better depiction of the distal vagina. © 2011 American Society for Reproductive Medicine.
Keywords: Adolescent gynecology; MRI; müllerian anomalies; vaginal septum